A ganância de Eustáquio e sua dragonicidade: tradução do romance de C. S. Lewis para o cinema - Silva, Francisca Elane Costa e (2024)
Eustace is a character from the book The Journey of the Dawn Treader (1952), one of C. S. Lewis's seven books in The Chronicles of Narnia, and also from the movie of the same name, produced by Walden Media and Fox in 2010 and directed by Michel Apted. This research compares the transformation of Eustace into a dragon, in the literary version and in the film. The main guiding principle of this study is based on Plaza's (2013) concept regarding thinking as translation, and focuses on the way Lewis conducts his writing process. For him, images always come first (LEWIS, 2018), which shows the author's innovative and creative potential as a translator of mental images. Thus, the analysis follows the process of retelling the story based on the criteria of retextualization, as the adapters tell stories in their own unique style (HUTCHEON, 2013). In this contrastive study between the two works, the highlighted excerpt is about the different aspects of Eustace’s monstrosity, which is manifested in his own qualities and personal interests, related to his transformation into a dragon. This character resembles the tale of Fáfnir (LANGER, 2013) who, corrupted by a treasure, turns into a dragon to guard it. Eustace's greed drives him down the same path of metamorphosis, which is not the path of death, but of a journey.